Supersonic Laser Deposition of Tungsten - LUPOI, ROCCO (My University, 2014)
Near fully dense tungsten coatings onto molybdenum substrates have been demonstrated using the Supersonic Laser Deposition (SLD) process. This is a characteristic that is not readily achievable with refractory materials. The tensile st rength of the tungsten deposited coatings is similar to that of wrought tungsten, with no evidence of melting or substrate grain growth. The tungsten coating to a molybdenum substrate shows no evidence of melting or substrate grain growth. The SLD process is a novel deposition method that is based upon Cold Spay (CS) principles. In this technique the deposition velocities can be significantly lower than those required for effective bonding in CS processing. The addition of laser heating alters the mechanical properties of the materials at the deposition site. The results have shown that SLD is able to deposit tungsten with unique interface bonding and desirable properties as opposed to other deposition processes for refractory materials
ASME 2014 Manufacturing Science and Engineering Conference (MSEC 2014)
PUBLISHED
Detroit, USA, 9-13 June
Keywords: Bend Test; Coatings; Tungsten; Supersonic Laser Deposition; Cold spray